The impact of COVID-19 on the employment status and psychological expectations of college graduates: Empirical evidence from the survey data of Chinese recruitment websites - Mao, Yufei; Zhang, Yuan; Bai, Jiaxin; Zhang, Liangbo; Hu, Wenxin (Frontiers in Psychology, 2022)
Based on the big data and survey data of online recruitment platform, this paper empirically tests the impact of COVID-19 on the employment status and psychological expectations of college graduates. The results show that: under the impact of COVID-19 epidemic, both supply and demand sides of college graduates' employment market are affected, such as the decline of recruitment demand, the rise of the employment supply, and the obvious decrease of employment market prosperity. The impacts of COVID-19 epidemic on college graduates' employment status and psychological expectation in different cities are heterogeneous. In the short term, the epidemic has a negative impact on the employment of graduates, but the employment situation is gradually improving with the support of national policies. Under the influence of COVID-19 epidemic, graduates will change their employment location and expected salary, and they tend to choose "temporary non-employment", and their proportions of getting offers and signing contracts are significantly reduced. This paper suggests: Firstly, we should continue to push forward the action plan of "expanding jobs in graduation season to promote employment", and strengthen the persistence and permanence of employment promotion policies for college graduates; Secondly, encourage college students to change their employment concept and rationally adjust their employment expectations; Thirdly, to promote the development of flexible employment of college graduates, it is necessary to strengthen the propaganda of flexible employment, so that students can understand relevant policies; Fourthly, strengthen employment guidance services for graduates from poor families to ensure the continuity and stability of employment assistance policies.